2017
DOI: 10.2147/ijwh.s125133
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychological distress among young women in Kisumu, Kenya

Abstract: BackgroundAttention to mental health issues is growing globally. In many countries, including Kenya, however, assessment of psychological distress, especially in rural areas, is limited.MethodsWe analyzed data from young women screened for a longitudinal contraceptive ring study in Kisumu, Kenya. Multivariable regression analysis was used to assess factors associated with recent moderate and high psychological distress, as measured by the Kessler (K-6) psychological distress scale.ResultsAmong the 461 women sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…We found that male adolescents were less likely to experience psychosocial distress than females. This observation could be because female adolescents are more prone to sexual abuse and harassment or exploitation which have negative implications for psychosocial distress [ 16 , 41 ]. Besides, the lower odds of psychological distress observed among males could be explained by the fact that male adolescents are more likely to form peer groups and are also more likely to confide in their friends, which helps them to mitigate the emotional problems which characterise adolescence [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that male adolescents were less likely to experience psychosocial distress than females. This observation could be because female adolescents are more prone to sexual abuse and harassment or exploitation which have negative implications for psychosocial distress [ 16 , 41 ]. Besides, the lower odds of psychological distress observed among males could be explained by the fact that male adolescents are more likely to form peer groups and are also more likely to confide in their friends, which helps them to mitigate the emotional problems which characterise adolescence [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the US National Longitudinal Study of Adolescent Health found that single and social-parent family structure is adversely associated with emotional adjustment, depression, adolescent delinquency, cognitive skills, school engagement, school problems, and grade point average [ 13 15 ]. Individual and socio-cultural factors such as female sex, lower formal education and lower socio-economic status, lack of social support, and stressful life events have also shown to be important contributors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, items had to be highly endorsed by fewer than 40% of non-cases (or 40% of cases for positive valence items). Because general distress is endorsed at high levels despite absence of mental disorder in settings like Kenya (Gust et al, 2017), we used a higher level of non-case endorsement than the typical 25%. Second, items needed to have a gradient score greater than 0.25, as lower scores indicated that an item showed poor or no discrimination between cases and non-cases.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression is high among pregnant women, with worldwide estimates of 11% to 18% [ 1 , 2 ] and is estimated to be between 15% to 28% in Lower- and Middle-Income Countries (LMICs) [ 3 ]. Studies in Kenya and neighboring countries have found that younger women (aged 18–24 years) experience greater psychological vulnerabilities [ 4 ] and depression in this group ranges from 8.3% to 39% [ 5 7 ] with high risk populations like adolescent mothers and gender-based violence impacted women [ 8 ]. Young women in Sub-Saharan Africa (SSA) lose around 10.4 disability adjusted life years due to depression during pregnancy.…”
Section: Introductionmentioning
confidence: 99%